Selang Kepercayaan Bootstrap Parametrik untuk Perbedaan Signal to Noise Ratio dari Distribusi Eksponensial Dua Parameter pada Data Waktu Kegagalan Laminasi Mylar-Poliuretana - Amirul Mukminin; Abdul Kudus (Bandung Conference Series: Statistics, 2023)
Abstract. The two-parameter exponential distribution is a probability model associated with observed unit failure time data. Investigating the estimation characteristics of the Signal to Noise Ratio (SNR) difference between two populations with a two-parameter exponential distribution is intriguing. SNR represents the ratio between the mean and standard deviation. For more accurate results in estimating the SNR difference between two populations, confidence intervals can be utilized. One of the methods suitable for constructing confidence intervals is the parametric bootstrap method, particularly effective for small sample sizes with distribution assumptions. The confidence intervals built are based on bootstrap percentiles. The data used in this study consists of small-sized samples of failure times of mylar-polyurethane lamination in High Voltage Direct Current (HVDC) insulation structures, subjected to voltage loads of 100.3 kV/mm and 361.4 kV/mm. Based on the calculations, it was found that with a 95% confidence level, the parametric bootstrap confidence interval for the SNR difference of the two-parameter exponential distribution of failure times in mylar-polyurethane lamination under electric voltage loads of 100.3 kV/mm and 361.4 kV/mm falls within the range of [-0.29; 0.93]. Abstrak. Distribusi eksponensial dua parameter adalah model probabilitas yang terkait dengan data waktu kegagalan unit yang diamati. Karakteristik dari estimasi perbedaan Signal to Noise Ratio (SNR) dari dua populasi berdistribusi eksponensial dua parameter menarik untuk diteliti. SNR adalah rasio antara rata-rata dengan simpangan baku. Untuk hasil yang lebih akurat dalam memperkirakan estimasi perbedaan SNR dari dua populasi yaitu menggunakan selang kepercayaan. Salah satu metode yang dapat digunakan dalam membangun selang kepercayaan yaitu dengan metode bootstrap parametrik yang cocok untuk ukuran data sampel yang kecil dan memiliki asumsi distribusi. Selang kepercayaan yang dibangun didasarkan pada bootstrap persentil. Data yang digunakan adalah data sampel berukuran kecil yaitu waktu kegagalan laminasi mylar-poliuretana pada struktur isolasi High Voltage Direct Current (HVDC) dengan beban tegangan 100,3 kV/mm dan 361,4 kV/mm. Berdasarkan hasil perhitungan diperoleh bahwa dengan tingkat kepercayaan 95% selang kepercayaan bootstrap parametrik untuk perbedaan SNR dari distribusi eksponensial dua parameter pada data waktu kegagalan laminasi mylar-poliuretana dengan beban tegangan listrik 100,3 kV/mm dan 361,4 kV/mm adalah berada di dalam rentang [–0,29; 0,93].